2020
DOI: 10.1111/jpc.14983
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the psychological status of mothers of children with cystic fibrosis and the relationship between children's clinical status

Abstract: In this study, we aimed to determine the psychosocial status of primary care givers of children with cystic fibrosis (CF) and its relationship with the clinical scores of children with CF. Methods: Thirty-six patients with CF and their primary care givers were assessed. A personal information form, as well as the Parent Attitude Research Instrument, Maslach Burnout Inventory, Beck Depression Scale and modified Shwachman-Kulczycki Score, were used for data collection. Results: All the CF children's primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…33 In a study evaluating 36 children with CF, mothers of children with CF with frequent hospital visits or hospitalizations were found to be more overprotective, rejecting the role of homemaker, and experiencing marital conflicts. 34 In our study, marital conflict was higher in mothers of children with PCD with burnout and caregiver burden. Rejection of the role of homemaker was more common in mothers who had other children with chronic disease and in mothers with marital conflict.…”
Section: Discussionsupporting
confidence: 43%
“…33 In a study evaluating 36 children with CF, mothers of children with CF with frequent hospital visits or hospitalizations were found to be more overprotective, rejecting the role of homemaker, and experiencing marital conflicts. 34 In our study, marital conflict was higher in mothers of children with PCD with burnout and caregiver burden. Rejection of the role of homemaker was more common in mothers who had other children with chronic disease and in mothers with marital conflict.…”
Section: Discussionsupporting
confidence: 43%
“…34 In a study evaluating 36 children with CF, mothers of children with CF with frequent hospital visits or hospitalizations were found to be more overprotective, rejecting the role of homemaker, and experiencing marital conflicts. 35 In our study, marital conflict was higher in mothers of children with The nature of overprotection has been defined as exhibited protective behavior that is excessive in light of the child's developmental stage and has been associated with parental stress.…”
Section: T a B L E 1 Sociodemographic Features And Clinical Character...mentioning
confidence: 58%
“…In addition, problems in the marital relationship, the decrease in the life expectancy of the child, and the decrease in the time allocated to the family are significant sources of stress 34 . In a study evaluating 36 children with CF, mothers of children with CF with frequent hospital visits or hospitalizations were found to be more overprotective, rejecting the role of homemaker, and experiencing marital conflicts 35 . In our study, marital conflict was higher in mothers of children with PCD with burnout and caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the logistic regressions indicated that the presence of depersonalization was associated with high BDI-II scores, which agrees with previous studies indicating a relationship between depersonalization and symptomatology of depression and anxiety ( 41 ). Other studies have also previously related the presence of the symptoms of depression and depersonalization with other components of burnout syndrome such as emotional exhaustion ( 42 ). Moreover, marital status was also associated with personal accomplishment in this current work, which is consistent with a study conducted in Korea which found that marital status, gender, workload related to the care of patients with COVID-19, and the presence of the symptoms of anxiety and depression were able to predict emotional exhaustion.…”
Section: Discussionmentioning
confidence: 98%